Prevalence of mixed features in patients with first-episode depression: An exploratory multicentric study - Sandeep Grover; Swapnajeet Sahoo; Kshirod K. Mishra; Raman Deep; Naresh Nebhinani; Ranjan Bhattacharya; Jitender Aneja; Roy A. Kalivayalil; Seshadri S. Chaterjee; Vikas Menon; Alka A. Subramanyam; Varghese P. Punnoose; et al. (Indian Journal of Psychiatry)
Background and Aim: There is limited literature on the prevalence of mixed features in patients with depression, especially from countries in Asia. Our aim was to evaluate the prevalence of “mixed features” in patients with first-episode depression. Materials and Methods: Patients with first-episode depression were evaluated for the presence of mixed features as per the Diagnostic and Statistical Manual (DSM)-5 criteria. They were additionally evaluated on Hamilton Depression Rating Scale (HDRS) and Young Mania Rating Scale (YMRS). Results: About one-sixth (16%) of the patients fulfilled the DSM-5 criteria for the mixed features specifier. The most common manic/hypomanic clinical feature was increased talkativeness or pressure of speech, followed by elevated expansive mood (12.5%), and inflated self-esteem or grandiosity was the least common feature (8.7%). Those with mixed features had higher prevalence of comorbid tobacco dependence and psychotic symptoms. In terms of frequency of depressive symptoms as assessed on HDRS, compared to those without mixed features, those with mixed features had higher frequency of symptoms such as depressed mood, insomnia during early hours of morning, work and activities, agitation, gastrointestinal somatic symptoms, genital symptoms, hypochondriasis, and poorer insight. Conclusion: Mixed features specifier criteria were fulfilled by 16% patients with first-episode depression. This finding suggests that the extension of this specifier to depression can be considered as a useful step in understanding the symptom profile of patients with depression.